Valve in valve transcatheter aortic valve implantation (ViV‐TAVI) versus redo—Surgical aortic valve replacement (redo‐SAVR): A systematic review and meta‐analysis. (20th May 2018) - Nalluri, Nikhil; Atti, Varunsiri; Munir, Abdullah B.; Karam, Boutros; Patel, Nileshkumar J.; Kumar, Varun; Vemula, Praveen; Edla, Sushruth; Asti, Deepak; Paturu, Amrutha; Gayam, Sriramya; Spagnola, Jonathan; et al.
Abstract : Background: Bioprosthetic (BP) valves have been increasingly used for aortic valve replacement over the last decade. Due to their limited durability, patients presenting with failed BP valves are rising. Valve in Valve − Transcatheter Aortic Valve Implantation (ViV‐TAVI) emerged as an alternative to the gold standard redo‐Surgical Aortic Valve Replacement (redo‐SAVR). However, the utility of ViV‐TAVI is poorly understood. Methods: A systematic electronic search of the scientific literature was done in PubMed, EMBASE, SCOPUS, Google Scholar, andClinicalTrials.gov . Only studies which compared the safety and efficacy of ViV‐TAVI and redo‐SAVR head to head in failed BP valves were included. Results: Six observational studies were eligible and included 594 patients, of whom 255 underwent ViV‐ TAVI and 339 underwent redo‐SAVR. There was no significant difference between ViV‐TAVI and redo‐ SAVR for procedural, 30 day and 1 year mortality rates. ViV‐TAVI was associated with lower risk of permanent pacemaker implantation (PPI) (OR: 0.43, CI: 0.21‐0.89; P  = 0.02) and a trend toward increased risk of paravalvular leak (PVL) (OR: 5.45, CI: 0.94‐31.58; P  = 0.06). There was no significant difference for stroke, major bleeding, vascular complications and postprocedural aortic valvular gradients more than 20 mm‐hg. Conclusion: Our results reiterate the safety and feasibility of ViV‐TAVI for failed aortic BP valves in patients deemed to be at high risk for surgery. VIV‐TAVI was associated with lower risk of permanent pacemaker implantation with a trend toward increased risk of paravalvular leak.